Considerations for the Medical Management of the Circus Performance Artist and Acrobat - John Faltus; Veronique Richard (International Journal of Sports Physical Therapy)
Medical management of the circus performer encompasses a wide variety of multicultural, transdisciplinary and multifaceted decision-making considerations. There is a paucity of research evidence investigating both the unique diversity of skill sets and cultural considerations in addition to injury patterns of performers within the circus environment. Since a previously established framework for supporting the health and well-being of the circus performer across various aspects of medical management does not exist in the literature, most recommendations in this regard must come from practical experience working with this highly specialized performance athlete population. The purpose of this clinical commentary is to provide the reader with a greater understanding of the unique challenges associated with the medical management of performance artists and acrobats as well as recommendations for developing an integrated approach for mitigating injury risk within a highly specialized, diverse athlete population.